Trends, patterns and psychological influences on COVID-19 vaccination intention: Findings from a large prospective community cohort study in England and Wales (Virus Watch). Issue 48 (26th November 2021) - Byrne, Thomas; Patel, Parth; Shrotri, Madhumita; Beale, Sarah; Michie, Susan; Butt, Jabeer; Hawkins, Nicky; Hardelid, Pia; Rodger, Alison; Aryee, Anna; Braithwaite, Isobel; Fong, Wing Lam Erica; et al.
Highlights: Intention to take a COVID-19 vaccine when offered is very high in England and Wales. Most people who were initially reluctant to accept a COVID-19 vaccine went on to change their mind. Young adults and people from some minority ethnic groups are more likely to be uncertain or plan to refuse a COVID-19 vaccine. Both perceptions of vaccines and perceptions of COVID-19 illness severity shape vaccine intention. Abstract: Background: Vaccination intention is key to the success of any vaccination programme, alongside vaccine availability and access. Public intention to take a COVID-19 vaccine is high in England and Wales compared to other countries, but vaccination rate disparities between ethnic, social and age groups has led to concern. Methods: Online survey of prospective household community cohort study participants across England and Wales (Virus Watch). Vaccination intention was measured by individual participant responses to 'Would you accept a COVID-19 vaccine if offered?', collected in December 2020 and February 2021. Responses to a 13-item questionnaire collected in January 2021 were analysed using factor analysis to investigate psychological influences on vaccination intention. Results: Survey response rate was 56% (20, 785/36, 998) in December 2020 and 53% (20, 590/38, 727) in February 2021, with 14, 880 adults reporting across both time points. In December 2020, 1, 469 (10%) participants responded 'No' or 'Unsure'. Of these people, 1, 266 (86%) changed their mind and responded 'Yes' or 'Already had a COVID-19 vaccine' by February 2021. Vaccination intention increased across all ethnic groups and levels of social deprivation. Age was most strongly associated with vaccination intention, with 16–24-year-olds more likely to respond "Unsure" or "No" versus "Yes" than 65–74-year-olds in December 2020 (OR: 4.63, 95 %CI: 3.42, 6.27 & OR 7.17 95 %CI: 4.26, 12.07 respectively) and February 2021 (OR: 27.92 95 %CI: 13.79, 56.51 & OR 17.16 95 %CI: 4.12, 71.55). The association between ethnicity and vaccination intention weakened, but did not disappear, over time. Both vaccine- and illness-related psychological factors were shown to influence vaccination intention. Conclusions: Four in five adults (86%) who were reluctant or intending to refuse a COVID-19 vaccine in December 2020 had changed their mind in February 2021 and planned to accept, or had already accepted, a vaccine.